2016
DOI: 10.1016/j.watres.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate removal and sulfur transformation in constructed wetlands: The roles of filling material and plant biomass

Abstract: Sulfate in effluent is a challenging issue for wastewater reuse around the world. In this study, sulfur (S) removal and transformation in five batch constructed wetlands (CWs) treating secondary effluent were investigated. The results showed that the presence of the plant cattail (Typha latifolia) had little effect on sulfate removal, while the carbon-rich litter it generated greatly improved sulfate removal, but with limited sulfide accumulation in the pore-water. After sulfate removal, most of the S was depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 36 publications
(63 reference statements)
6
38
1
2
Order By: Relevance
“…Sulfate removal efficiencies in CW is still unclear, some authors report low or negligible removal [54] while other studies reported high rates of sulfate removal [43,55]. It has been reported that the presence of T. latifolia had a marginal effect on sulfate removal, but its carbon-rich litter greatly promoted sulfate removal [56].…”
Section: Factors Involved In Metal Uptake Efficiencies By Plantsmentioning
confidence: 99%
“…Sulfate removal efficiencies in CW is still unclear, some authors report low or negligible removal [54] while other studies reported high rates of sulfate removal [43,55]. It has been reported that the presence of T. latifolia had a marginal effect on sulfate removal, but its carbon-rich litter greatly promoted sulfate removal [56].…”
Section: Factors Involved In Metal Uptake Efficiencies By Plantsmentioning
confidence: 99%
“…To date, all microorganisms mediating S-driven autotrophic denitrification have been affiliated with a-, 脽-, -, and 3-Proteobacteria (Shao et al 2010). Among them, Thiobacillus dentrificans and Sulfurimonas denitrificans are the most commonly studied and applied sulfide-dependent denitrifiers (Trouve et al 1998;Beller et al 2006aBeller et al , 2006bSievert et al 2008;Chen et al 2016).…”
Section: Sulfur Oxidizers Functioning As Denitrifying Bacteriamentioning
confidence: 99%
“…However, high concentrations of the chemicals are generally required for achieving significant decrease of cell retention. Many of these chemicals are resistant to biodegradation and have been considered as contaminants (e.g., SDS and SDBS), raising an issue of secondary pollution after the bioaugmentation effort [ Chen et al ., ; Cserh谩ti et al ., ; Li et al ., ; Liwarska鈥怋izukojc et al ., ]. In contrast, biosurfactants (surfactants produced by microbes) possess advantages of biodegradability and low toxicity [ Gautam and Tyagi , ; Liu et al ., ], and thus are more environmentally compatible.…”
Section: Introductionmentioning
confidence: 99%